2007
DOI: 10.1161/circulationaha.107.709360
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Programmed Death-1 Ligand 1 (PD-L1) Regulates CD8 + T-Cell–Mediated Injury in the Heart

Abstract: Background— PD-L1 and PD-L2 are ligands for the inhibitory receptor programmed death-1 (PD-1), which is an important regulator of immune responses. PD-L1 is induced on cardiac endothelial cells under inflammatory conditions, but little is known about its role in regulating immune injury in the heart. Methods and Results— Cytotoxic T-lymphocyte–mediated myocarditis was induced in mice, and the influence of PD-L1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
205
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(211 citation statements)
references
References 37 publications
3
205
1
2
Order By: Relevance
“…In this regard, it is interesting to note that PD-1-deficient mice develop spontaneously a lethal dilated cardiomyopathy on BALB/c background (52), due to autoantibodies directed against the cardiac muscle autoantigen, troponin I (53). Moreover, PD-1 ligand 1 (PD-L1), one of the two known ligands of PD-1, was recently shown to regulate CD8 ϩ T cell mediated injury in a mouse model of CD8 ϩ T cell-mediated myocarditis (54). In humans, PD-L1 was also shown to be expressed in muscle biopsy specimens of patients with polymyositis, dermatomyositis, or inclusion body myositis, especially in areas of strong inflammation (55).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is interesting to note that PD-1-deficient mice develop spontaneously a lethal dilated cardiomyopathy on BALB/c background (52), due to autoantibodies directed against the cardiac muscle autoantigen, troponin I (53). Moreover, PD-1 ligand 1 (PD-L1), one of the two known ligands of PD-1, was recently shown to regulate CD8 ϩ T cell mediated injury in a mouse model of CD8 ϩ T cell-mediated myocarditis (54). In humans, PD-L1 was also shown to be expressed in muscle biopsy specimens of patients with polymyositis, dermatomyositis, or inclusion body myositis, especially in areas of strong inflammation (55).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antigenpresenting cells, programmed death (PD)-1 receptors are present in cardiac endothelial cells, among which PD-L1 suppresses the cell-mediated immune response in acute myocarditis. 7 Abnormalities of cell-mediated immunity are also observed in DCM. It has been reported that suppressor T cells are decreased and helper T cells are increased in DCM patients, whereas increased MHC class II expression has been noted in studies of myocardial biopsy specimens.…”
Section: Abnormalities Of Cell-mediated Immunitymentioning
confidence: 99%
“…13 The known ligands for PD-1 are the B7 family molecules PD-L1 (B7-H1, CD274) and PD-L2 (B7-DC, CD273), [14][15][16][17][18][19][20] which are cell membrane-bound glycoproteins that share 40% amino acid homology to each other. In normal human tissues, PD-L1 is expressed by myeloid dendritic cells (DC), macrophages, placental trophoblasts, myocardial endothelium and cortical thymic epithelial cells, 21,22 whereas PD-L2 is expressed by DC, macrophages, placental endothelium and medullary thymic epithelial cells. 23,24 Binding of PD-1 to either ligand can inhibit T-cell proliferation and cytokine secretion.…”
Section: Introductionmentioning
confidence: 99%